Sosialisasi Business Model Canvass untuk Pengembangan Usaha Emping Melinjo di Desa Tegalwangi, Kecamatan Menes, Kabupaten Pandeglang - Tauny Akbari; Afni Khadijah (Universitas Mathla'ul Anwar Banten, 2020)
BUSINESS MODEL CANVASS SOCIALIZATION FOR DEVELOPING MELINJO CHIPS BUSINESS IN TEGALWANGI VILLAGE, MENES DISTRICT, PANDEGLANG REGENCY. Pandeglang Regency is an agropolitan area in Banten Province. Melinjo agricultural land area has the largest land area in this area, which is 1250 Ha. The large area of melinjo agricultural land is very supportive of the emping (chips) melinjo production business, especially in the District of Menes which has been designated as an Agropolitan area by the Government of Pandeglang Regency with the main income of emping melinjo. Entrepreneurs of emping melinjo can produce and sell 1-2 tons of emping melinjo every month. However, it still needs to be developed emping melinjo business based on the result analysis of business model canvas. The results of the analysis are conveyed through socialization to emping melinjo producent in Tegalwangi Village so that producents can develop their businesses more.